Grad Lušperk in njegovi prebivalci med 13. in 15. stoletjem - Bele, Martin (Acta Histriae, 2023)
The topic of this article is the little-known castle of Lušperk, the ruins of which lie some three kilometers northwest of Zreče. The article’s timeframe encompasses the thirteenth and fifteenth centuries. The estate on which the castle was built was originally owned by the Diocese of Gurk. The castle was first mentioned in 1279, as part of the name of a Henry (1279–1325), whose origin is unclear. Henrik may have been related to the Styrian ministeriales of Maribor or (much more likely) came from the retinue of the Counts of Heunburg. Considering his (still uncertain) ‘Heunburg pedigree’, Henrik was quite an exception among the many Styrian, Salzburg and Gurk ministeriales in his area of residence. According to the witness lists, he had contacts with members of the local nobility in Styria and Carinthia, but apparently never played an active role in these contracts. In addition to him, a man named Ulrich of Lušperk should be mentioned. In the 1330s, we trace Werner, Nicholas and Peter. While it is certain that Peter was Henry’s son, this cannot be said about Werner and Nicholas. We also come across a William who may have been a member of the clientele of the Counts of Celje. The final member of the family attested in the sources may be another Henry, mentioned in 1418. Other men, mentioned in connection to the castle later, no longer belonged to this family. In July 1439, Bishop John of Gurk paid Andrew Metz, the administrator of Lušperk, for the damage he suffered during the feud with the Counts of Celje. After that, Lušperk was apparently never rebuilt.
Keywords: Duchy of Styria; gospodje Mariborski; grofje Celjski; Habsburgs; Habsburžani; history; Krška škofija; Lušperk; Maribor; ne zaključna dela; vojvodina Štajerska; zgodovina Slovencev